Pemanfaatan Aplikasi dalam Jaringan pada Pembelajaran Jarak Jauh Mata Kuliah Tata Bahasa Mandarin - Andriani, Susi (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2022)
The Covid-19 pandemic has become a catalyst for changing learning models around the world, including the Mandarin Language Education Program (PSPBM) Faculty of Languages ​​and Arts, State University of Jakarta (FBS UNJ) which has also changed from a conventional (face-to-face) learning model to online distance learning.When the pandemic has ended, back to face-to-face learning in the classroom may be faced with the problem of limited time and space. Current technological developments can be considered and utilized as a solution, by developing online distance learning.One aspect that need to be considered on Developing online distance learning is the aspect of utilizing online applications that are used in learning activities. This article will specifically describe the results of research on the use of online applications in online distance learning activities during the pandemic for Mandarin Grammar Courses at PSPBM FBS UNJ.This research is a qualitative descriptive research. The data was obtained through interviews with supporting lecturers. Through this research, information was obtained that the online applications used were Whatsapp, Zoom, and Google Classroom. It is hoped that the explanation of the utilization, selection considerations, and the supervisor's views on these three applications can be considered by who will or who are developing online distance learning.